Disasters and minewater : good practice and prevention - Wood, Harvey (Integrated environmental technology series., 2012)
Disasters and Minewater: Good Practice and Prevention draws together all of the major minewater catastrophes that have occurred over the last half century. It examines incidents to find useful and positive information of great value that could prevent future disasters. Practical experience provides many lessons in respect of the causes of minewater incidents where lack of adhesion to good practice is principally to blame. Disasters and Minewater: Good Practice and Prevention is of particular interest to students of mining, civil engineering and environmental engineering. It is an invaluable resource for mining engineers, geotechnical engineers, environmental engineers and disaster relief professionals and consultants. Disasters and Minewater is a valuable complement to Minewater Treatment: Technology, Application and Policy by M Brown, B Barley, and H Wood, ISBN: 9781843390046. AUTHOR Harvey Wood, Clean Rivers Trust, UK Contents Introduction; Disasters and Minewater, Definitions, Occurrence, Locations, Calamities, The Main Issues, Subsidiary Issues, The Law and Regulation; Minewater and Rebound, Minewater Characterisation, Environmental Impacts of Minewater, Minewater Rebounds; Europe; North America; China; Asia; Pacific; Russia; South America; Law and Regulation; Tailings Dams; Floods and Inundation; Changes; Potential Future Catastrophe; Minewater Treatment; Global Investment and Minewater; Water Resource; In Conclusion.